The Effect Of Printing Speed And Nozzle Temperature On Tensile Strength, Geometry, and Surface Roughness Of A Product Printed using ABS Filament - Nurgesang, Faisal Arif; Dhewanto, Santo Ajie; Ridlwan, Muhammad; Paryanto, P (Prosiding Simposium Nasional Rekayasa Aplikasi Perancangan dan Industri, 2022)
3D printing is an additive manufacturing technology that can quickly create 3D models by softening thermoplastic filaments layer by layer. In making objects using 3D printing technology, there are several parameters that affect the strength of the printed objects, including the printing speed and nozzle temperature. This study aims to investigate effect of printing speed and nozzle temperature on tensile strength, geometry, and surface roughness of a product printed using ABS filament. The printing speeds were varied at 30, 40, and 50 mm/s while the nozzle temperature vaeried at 235, 245, and 255 oC. The tensile test was carried out on the printed specimens according to ASTM D-638-02a. The surface roughness and geometry tests were carried out on the printed specimen with dimensions of 30x30x40 mm. The surface roughness and geometry tests were performed on the vertical side in order to examine the layer and the change of height. The results concluded that the optimum printing speed and nozzle temperature based on the research conducted were 30 mm/s and 255 oC where the tensile strength as high as 33.52 MPa was obtained.